Physicochemical characterization and biological potential of Japanese quince polyphenol extract treated by different drying techniques. (December 2021) - Turkiewicz, Igor Piotr; Tkacz, Karolina; Nowicka, Paulina; Michalska-Ciechanowska, Anna; Lech, Krzysztof; Wojdyło, Aneta
Abstract: The aim of this study was to determine the effect of different drying methods – freeze drying, spray drying and vacuum drying (at 50, 70, 90 °C) – on the quality factors of Japanese quince polyphenol extract, including physical parameters, phenolic compounds, and in vitro biological activities (antioxidant, anti-diabetic, anti-obesity, and anticholinesterase). The highest content of bioactive compounds was observed in samples after freeze drying (total phenolic content – 912.7 g/kg dry weight [dw]; flavan-3-ols – 467.3 g/kg dw). The antioxidant activity measured by Oxygen Radical Absorbance Capacity (ORAC) assay was the highest for samples vacuum dried at 70 °C (1455.5 mol Trolox/kg dw). Moreover, strong anti-diabetic properties were obtained after vacuum drying, and the samples subjected to freeze drying and spray drying showed the most favorable anti-cholinergic potential. Unfavorable changes in color, formation of 5-hydroxymethylfurfural (5-HMF) and degradation of phenolics were noted along with the increasing drying temperature in vacuum drying. For vacuum drying, the most optimal temperature is 70 °C, as the final product obtained in this way is characterized by favorable physical properties, a beneficial content of biological compounds, a low concentration of undesirable 5-hydroxymethylfurfural and satisfactory biological properties. Graphical abstract: Image 1 Highlights: Japanese quince polyphenol extract (JQPE) is a rich source of flavan-3-ols. JQPE powders exhibit significantly higher antioxidant potential than ethanolic JQPE. Anticholinergic activity of JQPE powders was attributed to 5-hydroxymethylfurfural content.